Hubungan Proses Belajar Mengajar Berbasis Teknologi dengan Hasil Belajar: Studi Metaanalisis - Risnawita, Rini (Jurnal Psikologi, 2009)
This study was metaanalysis of the relationship between teaching and learning with technology and learning outcome. The quantitative review includes 43 studies from 12 articles that contained a combined sample of approximately 25150. This analysis extends previous work by directly correcting error of sampling and measurements. Summary analysis provided support that teaching and learning with technology has a correlation on learning outcome. The result showed teaching and learning with technology have been identified as predictors and learning outcome.